High-performance liquid chromatography of some natural dyes: analysis of plant extracts and dyed textiles - (:unkn) unknown (WILEY, 2012)
In this study, wool fibre samples were mordanted by means of 25% alum mordant solution. The mordanted wool samples were dyed in 50%Reseda luteola L. (weld), 20%Rhamnus petiolaris Boiss (buckthorn) and 50%Datisca cannabina L. (bastard hemp) dyebaths. A reverse-phase high-performance liquid chromatography with diode-array detection method was utilised for the identification of dyes in the dyed wool samples and the plant extracts. The extraction of dyes was carried out with a hydrogen chloride/methanol/water (2:1:1; v/v/v) mixture.
Keywords: RESEDA-LUTEOLA L.; DYEING PROPERTIES; IDENTIFICATION; HPLC; FLAVONOIDS